Ο εσωτερικός έλεγχος των ελληνικών επιχειρήσεων: εμπειρική προσέγγιση - Ζαφειράκου Ηλιάννα; Ταχυνάκης Παναγιώτης (SPOUDAI Journal of Economics and Business, 2007)
The purpose of this article is the empirical examination of internal auditing in the Greek companies. Emphasis is given in the way in which a department of internal auditing is created, the role of internal auditor towards the external auditors, the several departments of the company and the management, and finally the contribution and the composition of the auditing committee are examined. The results of the research convey that most of the companies consider the internal auditing of great importance for the satisfying and effective marching of a company. Hence, many companies have decided the implementation of a department of internal auditing, even if the alternative of hiring an internal auditor from an external auditing company promotes the reduction of the existing departments within the company and consequently of operation costs and expenses. Moreover, companies retain the independence and the responsibility and increase the internal auditor's efficiency, signaling the effectiveness of internal auditing. JEL Classification: M41